2006
DOI: 10.1021/ic061680v
|View full text |Cite
|
Sign up to set email alerts
|

Co(II)−Co(II) Paddlewheel Complex with a Redox-Active Ligand Derived from TTF

Abstract: A new trimethyltetrathiafulvalene (Me3TTF) derivative Me3TTF-CH=CH-py bearing a pyridyl was synthesized and coordinated to a cobalt(II) benzoate dimer, having paddlewheel core structure, leading to a complex formulated as Co2(PhCOO)4(Me3TTF-CH=CH-py)2. Single-crystal X-ray diffraction studies of the complex performed at 293 and 100 K evidenced the existence of a weak metal-metal interaction. Magnetic studies revealed an antiferromagnetic behavior, which is explained as the result of the direct exchange between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 25 publications
(14 reference statements)
5
51
0
2
Order By: Relevance
“…19. Molecular structure of Co5 [22]. distance of 3.56 Å, much longer than in the previous case (vide supra).…”
Section: The Co Rh Ir Triad With N-ligandsmentioning
confidence: 59%
See 2 more Smart Citations
“…19. Molecular structure of Co5 [22]. distance of 3.56 Å, much longer than in the previous case (vide supra).…”
Section: The Co Rh Ir Triad With N-ligandsmentioning
confidence: 59%
“…The second series of Co II complexes (Co5-Co7, Scheme 48) was reported by Ouahab et al and consists in the combination of [Co II 2 ] dimers [22] or [Co II 2 M II ] (M II = Co II , Mn II ) trimers [115] stabilized by bridging benzoate PhCOO − ligands, with monodentate TTF-ethenyl-pyridines 14a and 14b.…”
Section: The Co Rh Ir Triad With N-ligandsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have confirmed that we have formed the skeletal of our MOFs by the peaks obtained in between the wavelengths 1300 and 1650 cm −1 . Peaks at 1385 and 1589 cm −1 illustrate that TPA was attached successfully to the metal center …”
Section: A Possible Mechanism For the Widened Mesopores In Mil‐88b‐5mentioning
confidence: 99%
“…but in the range of Co···Co distances measured in other structures with Co 2 (RCOO)4 cluster[19][20][21][22]. The metal(II) PW clusters in 1 and 2 are bridged with BDC to form infinite polymeric 2-D (4 4 ) layers parallel to (1 0 2) planes with M 2 (CO 2 ) 4 as nodes (figure 1c).Each 2-D layer forms a square grid of ~ 10.58-10.58 Å 2 dimension and are stacked perpendicular to (1 0 2) planes with an offset which allows the pyridine molecules from the adjacent layers to fill the square aperture of the layer as shown in figure 2a.…”
mentioning
confidence: 99%